Comparison of chemical and functional components of different indica brown and germinated rice - LIU,Jiao (2022)
Abstract Nowadays brown rice (BR) and germinated brown rice (GBR) have aroused great interest of consumers, due to the higher nutrition compared with polished rice. In this study, the nutritional and bioactive compositions of BR and GBR samples prepared by 6 early indica rice cultivars and 12 middle indica rice cultivars from three producing areas were investigated. The free amino acid (215.75 mg/100 g), γ-aminobutyric acid (18.04 mg/100 g) and ferulic acid (195.9 μg/ g) content in early indica rice cultivars after germinated were significantly higher (P < 0.05) than those of other cultivars. In addition, principal component analysis and orthogonal partial least squares discriminant analysis models were able to identify BR and GBR, quercetin and p-coumaric acid were the most differential metabolites of all tested rice samples after germinated. The results provided the potential of early indica rice on functional food processing.